Are obese women potential for inflammatory process? A pilot study - Baghdad Science Journal (مجلة بغداد للعلوم)
This study was designed to look for certain biochemical markers(serum uric acid and serum peroxynitrite) in women presented with obesity and to compare the level of these markers with non-obese women. A total number of 63 women were recruited from outpatients and private clinics to admit in this study. The patients were grouped into non obese women (Group I) and obese women (Group II). The anthropometric and blood pressure were determined and venous blood was obtained from each patient for determination of C-reactive protein, uric acid and peroxynitrite. The results showed that there were no significant differences in age or in concomitant or associated diseases in both groups except rheumatoid arthritis which account 80% of group I and 25% of group II. The body mass index of Group I patients was 25.27±4.19 kg/h2 compared with 40.03±16.64 kg/h2 of Group II (p < 0.001). There were no significant differences in waist to hip ratio between two groups. The means systolic and diastolic blood pressures were higher in Group II compare with Group I. Positive C-reactive protein was observed in 53.3% and 52.1% of patients in Groups I and II respectively. Serum uric acid and peroxynitrite were non-significantly higher in Group II compared with Group I. It was concluded that obesity in women is associated with increased level of metabolic and nitrosative markers as well as alteration in inflammatory marker.